Derivatives law and regulation - Gengatharen, Rasiah (The Hague ; London Boston, Mass. : Kluwer Law International, 2001)
This book provides a straightforward and up-to-date analysis of the wide range of issues surrounding the use of derivatives in common law countries. It is the only work of its kind that focuses on derivatives law and regulation in Australia, New Zealand, Singapore, Malaysia and Hong Kong.
Includes bibliographical references and index.
oif 03/03/15, ijb 19/03/2019
Loan
Keywords: Derivative securities; Derivative securities; Derivative securities; Derivative securities; Derivative securities